Comparative in vitro Assessment of Tooth Color Change under the Influence of Nano Fast Cement and MTA - Fariborz Moazzami; Safoora Sahebi; Sareh Shirzadi; Niloufar Azadeh (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Tooth color changes followed by treatment with bioceramic materials are always a matter of concern. Purpose: The aim of the present in vitro study was to compare tooth discoloration that occurs in human teeth filled with ProRoot WMTA (DENTSPLY Tulsa Dental Specialties, Tulsa, OK) and those filled with Nano Fast Cement (NFC) over the course of 3 months. Materials and Method: In this experimental study, Thirty human intact premolars were obtained. The roots of all teeth were removed by a horizontal cut about 2 mm below the cementoenamel junction. The pulp tissues were removed using a barbed broach (Mani, Tokyo, Japan).The teeth were randomly divided to 3 groups (n= 10) including the control (no material), ProRoot WMTA and NFC. The experimental materials were condensed into the crowns and the teeth ends were sealed with light-cure glass ionomer cement (GC Corporation, Tokyo, Japan). The color was assessed at TBL (baseline; after preparation of the cavities but before placement of the materials), TPO (immediately after placement of the filling material and provisional restoration), T4 (after 4weeks of storage), and T12 (after 12weeks) of storage. Results: The discoloration was evident in all teeth, immediately (TPO) after applying MTA and NFC. The highest ΔΕ was noted in WMTA at 12 weeks, followed by NFC; however, there was no significant difference between the discolorations induced by these two materials. Conclusion: Similar levels of clinically observable tooth discoloration were detected by using either WMTA or NFC.